Efektivitas Penggunaan Permainan Dahi Detektif sebagai Game Edukatif dalam Intervensi Bencana Banjir dan Kebakaran pada Anak Usia 10-11 Tahun - Tiara Marsela Triyani; Harta Prima Meza; Lovina Ausha Nessaputri; Syukriat Syukriat; Qori Gheitsa Zahira; Devi Lusiria (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Indonesia has high vulnerability to floods and fires that cause psychological impacts on children. This study examined the effectiveness of the "Dahi Detective" game as an educational intervention among 25 fifth-grade students at SDN 29 Dadok Tunggul Hitam, Padang. A Game-Based Learning method was employed with data collection through observation, pre-post questionnaires, interviews, and field notes, then analyzed using Wilcoxon Signed-Rank test. Results showed significant improvement in disaster understanding (p < 0.001) with the mean pretest score increasing from 71.28 to 89.76 in the posttest with maximum effect size -1.000. The Dahi Detective game proved effective in enhancing children's understanding of flood and fire disaster causes, supporting constructivist and Bandura's social learning theories.